Examining Front-Line Administrative Services in a Selected Public Higher Education Institution - Mthokozisi Luthuli; Ntando Nkomo; Smangele Moyane (MDPI AG, 2024)
The South African government's commitment to people-friendly public service since 1994 has influenced the quality of service provided by front-line administrative staff in public higher learning institutions. This study explores the experiences of front-line administrative staff at the Durban University of Technology (DUT), focusing on the challenges faced and their impact on teaching, learning, and overall academic activities. Against the backdrop of public higher education institutions (HEIs) in South Africa, the study addresses the persistent challenges in service delivery and the crucial role of front-line administrative staff. Employing a post-positivist paradigm, the research adopts a hybrid methodological approach, combining qualitative and quantitative methods. A survey design is utilized to gather data from first-time entry students (FTENs) enrolled in the Business and Information Management program at DUT, employing convenience sampling and a self-administered questionnaire. The study's findings illuminate the inefficiencies in front-line administrative services, elucidating their impact on diverse stakeholders and emphasizing the pressing need for enhancement. The study found that the majority of students perceived the services positively, with only a small number expressing dissatisfaction and nearly all participants noted the institution's adherence to the Batho Pele Principles positively, though a few had contrasting experiences. The findings further revealed areas of improvement for the service. By focusing on the experiences of FTENs, the study contributes to the broader discourse on enhancing service delivery in public higher learning institutions. Addressing these challenges is crucial for the fulfilment of the core mission of HEIs providing quality education and fostering a positive learning environment.